Comparison of Hip Spica Cast vs Intramedullary Rush Nail Fixation in the Treatment of Femoral Shaft Fractures in Children - Allah Nawaz Abbasi, Zahoor Maid Soomro, Syed Karam All Shah, Saeed Shah , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To compare the results of bone union in hip spica cast versus rush nail fixation for fracture shaft of femur in children of age 2-12 years. Place & Duration: Department of Orthopedic Surgery Peoples University of Medical Heath & Sciences Nawabshah from January 2016 to December 2016. Methods: This randomized control trials was carried out in the department of orthopedic surgery Peoples University of medical Heath & sciences Nawabshah from January 2016 to December 2016. A total of 100 patients were included in the study. These were divided in two groups. In group A, children were treated with hip spica casting and in group B, children were treated with rush pin fixation. Results: Mean duration of fracture union was 12(13.25 +2.43 )weeks in group A and 10(10.76+ 0.72) weeks. Mean hospital stay was 3.32+ 1.4 days in group A and in group B it was 6.56+ 2.75 days. In group A,the mean follow up period was 16 months and in group B,it was 17 months. Conclusion: Close reduction and internal fixation with Rush pins is superior in terms of early mobilization, restoration of normal anatomy and scat of normal routine activity.